Effects of organizational culture on environmental management control system and performance of manufacturing firms in Pakistan - Bakhsh, Hussain (2018)
Although companies are continuously implementing the environmental discourse in their external reporting, yet, very fewer studies talk about how management control systems (MCS) support sustainability and environmental performance within organizations and embed in the organization. As a consequence of the worldwide environmental issues, companies are trying to start the environmental friendly practices. In response to the threats created by climate change and other environmental issues, companies are trying to prioritize sustainability as a core business issue. Many companies have already learned that sustainability can be a competitive advantage; however, in developing countries, the majority of companies in manufacturing industry have been failed to address these challenges. Therefore, the role of MCS is critical for the contemporary business arena as a source of controlling the behavior of employees and evaluating organizational resources for implementing strategies efficiently and effectively. Despite the fact that organizations continuously recognize environmental discourse in their external reporting, yet, a countable have discussed the importance of MCS that support sustainability and environmental performance within organizations. Existing literature reveals that organizational culture plays a vital role for successful implementation, yet little empirical research has been done to describe the relationship between organizational culture and MCA. In this context, this research fills this gap by investigating the role of organizational culture (OC) for development of environmental management control systems (EMCS) for better firm performance. Using survey data from a sample of Pakistan manufacturing firms, 314 responses were collected and analyzed by using Smart-PLS 3.2.6. Results suggest that flexible values of OC led to the development of the informal EMC, and stable values led to development of formal EMC. The formal and informal EMCS result in better firm performance. The results reveal that mediation of formal EMCS with the mission and environmental performance, and formal EMCS with the mission and social performance were not significant. The full mediation has been observed for consistency in its relationship with formal EMCS and economic and social performance and partial mediation in the relationship between formal EMCS and environmental performance. The most surprising aspect of an indirect impact of the mission on the environment and social performance which is not significant without any mediation and the only direct effect is significant. The relationship of involvement with economic and social performance is significant and positive. The relationship of involvement with environmental performance is not significant. The findings show that there is no significant impact of adaptability on economic, environmental and social performance. The consistency is also not significant with the relationship of firm performance. The findings reveal that mission is significantly associated with the environmental and social performance. The findings of this empirical research make three contributions. First, it demonstrates how companies align OC to develop an environmental culture that supports the development of EMCS, and that as a result improves firm’s performance. Based on the contingency theory, this study provides evidence that OC directly affects the design and use of MCS. The results further reveal that EMCS fully mediate the effect of OC on economic performance. Thus, EMCS can be used to translate environmental strategies into high firm performance, supporting earlier research with broad empirical evidence. Furthermore, this study contributes to the literature regarding environmental practices and sustainability. This study extends previous research on the effect of EMCS into a more traditional MCS. The current study’s results revealed that firm performance including the environmental performance is much higher when environmental aspects are integrated into a more traditional MCS. Third, the study demonstrates that integration of an environmental culture leads to more developed EMCS. Companies with substantial environmental issues (i.e., manufacturing industry in Pakistan) may develop strategies that seriously address environmental concerns and implement additional measures to improve their environmental performance.